2018
DOI: 10.18535/jmscr/v6i8.91
|View full text |Cite
|
Sign up to set email alerts
|

A Study about Demographic, Clinical, Comorbidity and lipid profile of hypothyroid patients attending a tertiary health care institute of Rajasthan

Abstract: Background: Hypothyroidism is a common disorder. It may emerge or worsen other comorbidities. This study was conducted to know demographic, clinical, comorbidity and lipid profile of hypothyroid patients in Rajasthan in order to understand current scenario and to know desired improvement in strategy. Method: This cross sectional study was conducted for the duration of six months. One hundred and three hypothyroid patients participated in the study. Thirteen patients were drop outs and ninety participated activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…[44] In the current study, overall prevalence of SCHypo is found to be 33.75%, which coincides with many studies. [29,36,45,46] In our study, SCHypo was common in the age group of 60-79 (57.6%, 109/189). Similar observations were reported in few studies [20,35] few studies reported lower age groups in this context.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…[44] In the current study, overall prevalence of SCHypo is found to be 33.75%, which coincides with many studies. [29,36,45,46] In our study, SCHypo was common in the age group of 60-79 (57.6%, 109/189). Similar observations were reported in few studies [20,35] few studies reported lower age groups in this context.…”
Section: Discussionsupporting
confidence: 51%
“…[27][28][29][31][32][33][34][35] Results of current study as well as previous studies support the fact that hypothyroidism is more common in females. [36] In most of studies the thyroid disorders were common in the age group between 20 and 45, [37,38] but we observed a higher proportion within 50-79. This variation may be due to the fact that we have included only those subjects who underwent CABG, which is more pervasive in higher age groups.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…The goal of the study is to clarify these links in order to improve patient care for patients with thyroid dysfunction as well as clinical practices and treatment techniques. [13,14,15]…”
Section: Introductionmentioning
confidence: 99%